Kosovo : Policy Note on Public Investment Management - World Bank (Washington, DC, 2012)
As Kosovo moves towards resolution of its political status, the attention of the authorities and of the international donor community is increasingly turning towards the need for modernization of Kosovo's economic and social infrastructure in order to facilitate sustained economic growth and development. This note looks further into the underlying causes and the actions that will be required to address them. The main conclusions of the note are that the fundamental causes of under spending on the capital spending program lie in the failure to plan and manage the program within a medium-term context and in the institutional capacity constraints that currently confront the public finance management (PFM) system. The note begins by providing a brief overview of the scale and composition of Kosovo's capital spending program (section B) and the institutional arrangements for public investment management (section C). It then goes on to look at the causes of the fall in the execution of the capital spending budget that occurred in 2006 (section D), and to consider in more detail issues relating to capital investment identification and development (section E), budget preparation and financing (section F), and capital budget execution, procurement and monitoring (section G). The final section summarizes the key conclusions and next steps actions (section H). A summary of the analysis is provided in the assessment framework that is included in annex I.